1969
DOI: 10.5962/bhl.title.47225
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology and sediments of the nearshore continental shelf : Miami to Palm Beach, Florida / by David B. Duane, Edward P. Meisburger.

Abstract: Woods Hole Oceanographic Institution The Continental Shelf bordering southeastern Florida between Palm Beach and Miami was surveyed by the U. S. Army Coastal Engineering Research Center to locate and evaluate sand deposits potentially usable for shore protection and restoration projects. Survey data covered that portion of the Continental-Shelf between 15-and 100-foot depths, and consisted of seismic reflection profiles and sediment cores of the sea floor and shallow subbottom strata. South of Boca Raton to Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Another feature of the main teleconnection patterns is the interaction between particular oscillations. This interaction appears to be nonlinear and seems, to some extent, to be partially synchronized chaos (as was found by Duane et al (1999) for the northern and southern hemisphere blocks). For such a complex system, the only possibility for realistic modelling seems to be when only a few of the various mechanisms become prevalent in the process, so that the system dynamics are simplified with a corresponding reduction in the number of the effective degrees of freedom.…”
Section: Introductionsupporting
confidence: 52%
“…Another feature of the main teleconnection patterns is the interaction between particular oscillations. This interaction appears to be nonlinear and seems, to some extent, to be partially synchronized chaos (as was found by Duane et al (1999) for the northern and southern hemisphere blocks). For such a complex system, the only possibility for realistic modelling seems to be when only a few of the various mechanisms become prevalent in the process, so that the system dynamics are simplified with a corresponding reduction in the number of the effective degrees of freedom.…”
Section: Introductionsupporting
confidence: 52%
“…We have previously reported that ascorbate/Fe2-induced oxidative stress potentiates the NMDA-receptor activity due to the release of AA (17). Free arachidonic acid was shown to inhibit the activity of the glutamate transporter by binding either to the transporter protein or to the protein-lipid boundary (34,54,55). However, arachidonic acid seems not to be involved in the inhibition of D-[3Hlaspartate uptake under the oxidative stress conditions used here, since the preincubation of cells with the PLA2 inhibitor ONO-RS-082 or the fatty acid chelator BSA had no significant effect on the activity of the transporter, both in control and in peroxidized cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The exploration program is conducted through the U. S. Army Coastal Engineering Research Center (CERC) . An initial phase in developing techniques for transferring offshore sand to the beach is described by Mauriello (1967) the information collected in the conduct of the research program toward the CERC mission, especially in terms of Continental Shelf structure (Meisburger and Duane, 1969), Continental Shelf Sedimentation (Field, Meisburger and Duane, 1971), and its potential application to historical geology and engineering studies of the shelf, the sand inventory program is now referred to as the Inner Continental Shelf Sediment and Structure Program (ICONS).…”
Section: Introductionmentioning
confidence: 99%